Knowledge, attitude and practices related to prevention of parasitic infestations among school children in an urban area of Kancheepuram district - Hariharan, S. (International Journal Of Community Medicine And Public Health, 2019)
Background: Poor hygiene practices and inadequate sanitary conditions play an important role in the increased burden of communicable diseases in developing countries. The aim and objectives of the present study was to assess the knowledge, attitude and practices related to prevention of parasitic infestations among school children in an urban area of Kancheepuram district. Formulation of suitable preventive measures based on the inferences derived from the study. Methods: A cross-sectional study was done on school children belonging to standard sixth to eighth of Sree Lakshmi Ammal school, Chrompet. The study period was from August 1st to 4th 2018. The sample size obtained was 210. Convenient sampling method was used to collect the sample. A pre-tested structured questionnaire was used to collect the data regarding knowledge, attitude and practices related to prevention of parasitic infestations among school children. Assessment of personal hygiene was done by scoring system. Data entry was done in Microsoft Office Excel 2007 and data was analysed by SPSS version 22. Results: Total number of children participated in the present study were 210. Among the children participated in the present study, 92.4% of children had a good knowledge of personal hygiene, 96.7% of children had a positive attitude towards personal hygiene and 81.4% of children had a good practice of personal hygiene. Conclusions: Nearly half of the children involved in the study practised open defecation, so they should be given proper health education regarding usage of sanitary latrines.